PENERAPAN METODE DIARY WRITING BERBASIS ICT DENGAN MEMANFAATKAN INSTAGRAM STORY UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PENULISAN CERPEN KELAS VIII C DI SMP NEGERI 4 KUTA UTARA - Pinatih, Ni Luh Eka Purnami; Susrawan, I Nyoman Adi; Wedasuwari, Ida Ayu Made (Prodi Pendidikan Bahasa dan Sastra Indonesia FKIP Unmas Denpasar, 2024)
This research is Classroom Action Research (PTK) which aims to (1) Describe the learning outcomes of students VIII C of SMP Negeri 4 North Kuta on critical thinking skills in short story writing after implementing the ICT-based Instagram Story diary writing method; (2) Describe the steps of the Instagram Story ICT-based diary writing method which is effective for improving the critical thinking skills of VIII C students in short story writing; (3) Analyzing the results of student VIII C's responses to the ICT-based Instagram Story diary writing method on short story writing skills. Data collection was carried out using observation, tests and questionnaires. The data obtained was analyzed descriptively qualitatively and quantitatively. The results and responses of students are qualitatively quantitative while the learning steps are qualitative. The results of the research show that the application of the Instagram Story ICT-based diary writing learning method is able to improve critical thinking skills in short story writing in class VIII C students who have been tested according to the success indicators of this research. The increase in these skills can be seen from the enthusiasm of students when learning is collaborated with ICT in the form of social media Instagram, students begin to be active in the learning steps, namely (1) topic delivery stage, (2) discovery, (3) imaginative, (4) analyze, (5) reality, (6) yourself, (7) consultation stage, (8) writing assignment, (9) testing stage and (10) evaluation stage that have been carried out in this diary writing method, this improvement can also be seen from the results of short story writing skills using creativity obtained from Instagram through imagination that is linked to students' daily lives. Evidenced by the increase in student learning outcomes in the pre-cycle with a score of 65, classical completeness only had a score of 9.3%, in the first cycle the students managed to get a score of 73 with classical completeness being 37.5%, in the second cycle with an average class score namely 90.5 with 100% classical completeness. With student response results of 96.8% in the very good category.